Comparison of Turbo Flash and dual-energy modes of third-generation dual-source CT in pre-transplant renal angiography: a prospective observational study - Navya Christopher; Gopinath Periaswamy; Venkatesh Kasi Arunachalam; Vandana Pilli; Rupa Renganathan; Sriman Rajasekaran; Pankaj Mehta; Mathew Cherian (The Egyptian Journal of Radiology and Nuclear Medicine, 2022)
Abstract Background The purpose of this study was to compare the Image Quality, Contrast Medium Volume, and Radiation dose in renal angiography performed using Turbo Flash mode and dual-energy (DE) mode in the third-generation dual-source dual-energy CT. This prospective observational study was performed on renal donors who underwent CTA imaging as a pre-transplant workup. The study population was divided into two groups. Group A underwent DECT renal angiography. Group B underwent Turbo Flash Mode CT renal angiography. For group A, a contrast volume of 1 ml/kg and for group B at 0.5 ml/kg was administered. Image Quality was evaluated objectively by calculating CNR and SNR and subjectively by a 5-point scale. Radiation Dose analysis was done by noting CTDIvol and DLP on the scanner system and calculating effective radiation dose (ED). Results The subjective image quality scores for the Turbo Flash group were comparable with the DE group in qualitative image analysis. Additionally, in the Turbo Flash group, there was a reduction in contrast media and effective radiation dose by 47.5% and 32.7%, respectively. Nevertheless, mean attenuation of the abdominal arteries, CNR, SNR, and Noise (S.D) showed statistical significance between the two groups (p value < 0.01). Conclusions To our knowledge, no previous study compared Turboflash mode with DE protocol in CT renal angiography in a donor group of patients. Turbo Flash CT is an excellent modality that is faster and has an added advantage of decreased radiation dose and contrast media volume reduction, which can be recommended for screening of voluntary kidney donors but needs further clinical studies, validation, and standardization with tailored protocols.